2014
DOI: 10.1090/s0002-9947-2014-06115-1
|View full text |Cite
|
Sign up to set email alerts
|

Computable completely decomposable groups

Abstract: Abstract. A completely decomposable group is an abelian group of the form i H i , where H i ≤ (Q, +). We show that every computable completely decomposable group is ∆ 0 5 -categorical. We construct a computable completely decomposable group which is not ∆ 0 4 -categorical, and give an example of a computable completely decomposable group G which is ∆ 0 4 -categorical but not ∆ 0 3 -categorical. We also prove that the index set of computable completely decomposable groups is arithmetical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Only recently, there has been significant progress in understanding Δ 0 n -categoricity in several specific classes, for small n. It follows from [8,30] that every free (non-abelian) group of rank ω is Δ 0 3 -categorical, and the result cannot be improved to Δ 0 2 . It is also known that every computable completely decomposable group is Δ 0 5 -categorical, and the result is sharp [13]. Every computable homogeneous completely decomposable group is Δ 0 3 -categorical, and a group of this form is Δ 0 2 -categorical if and only if it encodes a semi-low set into its divisibility relation [12].…”
Section: Non-computable Isomorphisms Between Computable Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Only recently, there has been significant progress in understanding Δ 0 n -categoricity in several specific classes, for small n. It follows from [8,30] that every free (non-abelian) group of rank ω is Δ 0 3 -categorical, and the result cannot be improved to Δ 0 2 . It is also known that every computable completely decomposable group is Δ 0 5 -categorical, and the result is sharp [13]. Every computable homogeneous completely decomposable group is Δ 0 3 -categorical, and a group of this form is Δ 0 2 -categorical if and only if it encodes a semi-low set into its divisibility relation [12].…”
Section: Non-computable Isomorphisms Between Computable Structuresmentioning
confidence: 98%
“…The study of Δ 0 n -categorical structures has some independent technical interest as such investigations typically require new ideas and techniques (see, e.g., [2,12,13]). As a consequence of these technical difficulties, our knowledge of Δ 0 n -categorical structures is rather limited even when n = 2.…”
Section: Non-computable Isomorphisms Between Computable Structuresmentioning
confidence: 99%
“…Downey and Melnikov ( [3], [4]) studied homogeneous completely decomposable groups, in which each summand has the same type (see Definition 2.2). They found that every completely decomposable group is ∆ 0 5 -categorical, but homogenous completely decomposable groups are actually ∆ 0 3 -categorical.…”
Section: Introductionmentioning
confidence: 99%
“…In their research of completely decomposable groups, Downey and Melnikov [4] found that the index set of completely decomposable groups can be described by a Σ 0 7 formula (though it is not known if this is sharp). The property with which this paper is concerned is a similar one: decomposability.…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that our metatheorem has relativized and generalized versions that could be applied to, say, completely decomposable groups [DM14,Khi02] and other structures where the notions of independence are not r.i.c.e. but are relatively intrinsically Σ 0 n for some n > 1.…”
mentioning
confidence: 99%